Association of serum uric acid, morning home blood pressure and cardiovascular risk factors in a population with previous prehypertension: a cross-sectional study. Issue 9 (9th September 2020) - Bawazier, Lucky Aziza; Sja'bani, Mochammad; Irijanto, Fredie; Zulaela, Zulaela; Widiatmoko, Agus; Kholiq, Abdul; Tomino, Yasuhiko
Abstract : Objective: To observe the changes in blood pressure (BP) over 10 years and to investigate current BP association to serum uric acid (SUA) levels and cardiovascular risk factors in the epidemiological data of a target group of patients with prehypertension in 2007. Design: Cross-sectional study. Setting: Mlati Subdistrict, Sleman District, Yogyakarta Province, Indonesia. Participants: A total of 733 patients from 'Mlati Study Database' in 2007 were selected by simple random sampling using statistical software. Subjects had both physical and laboratory examinations. Outcome measures: Morning home BP and laboratory examination of urine (uric acid excretion and creatinine) and blood samples (SUA, blood urea nitrogen, creatinine, a lipid profile and fasting blood glucose levels). Results: About 31.1% of 733 subjects with prehypertension became hypertensive after 10 years, 24.6% returned to normal tension and the rest of it remained in prehypertensive state. Mean (SD) of SUA levels in 2017 was significantly higher in men than in women (5.78 (1.25) mg/dL vs 4.52 (1.10) mg/dL, p<0.001). Furthermore, men tended to have high-normal (5–7 mg/dL) or high SUA levels (≥7 mg/dL) compared with women (p<0.001, Relative Risk (RR)=2.60). High-normal and high SUA levels in population with a history of prehypertension were significantly associated with current prehypertension and hypertension only in women (p=0.001, RR=1.21). Age and body mass index was found to be significantly associated with both systolic and diastolic BP in men, but only with systolic BP in women. Fasting blood glucose and SUA levels were significantly associated with systolic and diastolic BP only in women. Conclusion: We concluded that after 10 years, of 733 subjects with prehypertension, 31.1% became hypertensive. The SUA levels in men are significantly higher than those in women. Moreover, high-normal and high SUA levels were significantly associated with prehypertension and hypertension in women but not in men.